Relasi Pemerintah dan Akademisi dalam Isu Moderasi Beragama di Indonesia - Abdul Malik; Busrah Busrah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Religious moderation is one of the government's important agendas and commitments to realize a peaceful Islam, including through intellectual movements in the form of seminars, academic presentations, and scientific publications. The focus of this article is the mapping of research/academic writings by Islamic academics in the study of religious moderation. Data collection was carried out through a literature review by analyzing research publications among academics related to the theme of religious moderation. The analytical framework used in this article is discourse analysis and dialectics. This study concludes that some of the dominant themes published are: (a) The theme of religious moderation within the Indonesian-National scope. The discourse developed is Islamic moderation and Cultural Society. (b) The theme of religious moderation is da'wah broadcasts. The discourses raised are moderation and social media. (c) The theme of religious moderation of social organizations and ideological groups. The discourse that was raised was about the Islamic Moderatism of NU and Muhammadiyah. (d) The theme of Religious Moderation in Educational Institutions. The discourse that emerged was that Pesantren builds Moderation and Internalization of Moderation Values. The discourse analysis in this article shows that the article on Islamic Moderation is an expression or response of academics in viewing the reality and state of social policy around it. The Ministry of Religion as politicians and academics from several Islamic campuses under the Ministry of Religion have mutually supportive relationships in this issue of religious moderation Abstrak:. Moderasi agama merupakan salah satu agenda dan komitmen penting pemerintah untuk mewujudkan islam yang rahmatan lil ‘alamin, salah satunya melalui gerakan intelektual berupa: seminar, presentasi akademik dan publikasi Ilmiah. Fokus artikel ini adalah pemetaan terhadap riset/tulisan akademik para Akademisi Islam dalam kajian moderasi beragama. Penggalian data dilakukan melalui kajian kepustakaan dengan menganalisa publikasi riset dikalangan akademisi terkait dengan tema moderasi beragama. Kerangka analisis yang digunakan dalam artikel ini adalah analisis wacana dan dialektika. Penelitian ini menyimpulkan bahwa beberapa tema dominan yang dipublikasi adalah : (a) Tema Moderasi beragama dalam lingkup Nasional-Keindonesiaan. Wacana yang dimunculkan yakni moderasi Islam dan Masyarakat Kultural. (b) Tema Moderasi beragama siaran dakwah. Wacana yang dimunculkan yakni moderasi dan Media Sosial. (c) Tema Moderasi beragama organisasi Kemasyarakatan dan kelompok Ideologi. Wacana yang dimunculkan seputar Moderatisme Islam NU dan Muhammadiyah. (d) Tema Moderasi beragama Instansi Pendidikan. Wacana yang dimunculkan yakni Pesantren membangun Moderasi dan Internalisasi Nilai Moderasi. Analisis wacana dalam artikel ini menunjukkan bahwa artikel mengenai Moderasi Islam merupakan sebuah ekspresi atau respon akademisi dalam memandang realitas dan keadaan kebijakan sosial di sekitarnya. Kementerian Agama sebagai Politisi dan akademisi dari beberapa kampus Islam di bawah kementerian Agama memiliki relasi yang saling mendukung dalam isu Moderasi beragama ini.